129 Evaluation of Cardiac Risk Using Dobutamine Cardiac Stress Magnetic Reasonance Prior to Renal Transplantation. (6th June 2015) - Swarbrick, Daniel; Bellenger, Nick; Kannoly, Sri; Gosling, Oliver; Hossain, Ejaz; Shore, Angela; Chawner, Rebecca; Ripley, David
Abstract : Background: Coronary artery disease (CAD) is common in patients with end-stage renal disease, and remains a major cause of death in patients undergoing renal transplantation. There is a high prevalence of silent CAD in these patients. Current guidelines recommend a screening test is performed for CAD as part of cardiac assessment prior to renal transplantation. Dobutamine stress cardiac MRI (DSCMR) has been shown to be useful in providing prognostic stratification in the general population at risk of CAD, but has not yet been evaluated in patients awaiting renal transplantation. We sought to establish the prognostic value of DSCMR in this population. Methods: 76 patients with end-stage renal disease being considered for renal transplantation underwent DSCMR as part of their cardiac evaluation. 67 patients had a diagnostic study (attaining at least 85% of maximal, age-predicted heart rate, or the presence of inducible wall motion abnormalities) and were included in the final analysis. Clinical follow up was performed for a mean of 578 (+/- 308) days, and cardiac events (cardiac death, non-fatal myocardial infarction, urgent revascularisation) were recorded, as well as the outcome of any patients that underwent renal transplantation. Results: Retrospective analysis of clinical outcomes was performed on the 67 patients who completed a diagnostic DSCMR study. The average age was 56 +/-11, 67% were men, 67% were dialysis-dependent, 76% had hypertension and 31% had diabetes mellitus. 6 patients (9%) had DSCMR with resting (fixed) regional wall motion abnormalities (RWMA), 6 patients 99%) had new RWMA with dobutamine stress, and 55 (88%) were normal studies. There were no cardiac deaths. 2 patients had non-fatal myocardial infarction. Both of these events occurred in patients with fixed RWMA. The presence of fixed RWMA (p = 0.007) or a history of prior myocardial infarction (p = 0.008) were predictive of adverse cardiac events. No major adverse cardiac events occurred in any of the 55 patients with normal DSCMR during follow up, with only 1 elective revascularisation (negative predictive value 98%, 95% CI 90–100%). 16 patients (14 with normal DSCMR, 1 with resting RWMA and 1 with stress-induced RWMA) had undergone renal transplantation at the time of writing, with no adverse cardiac events. Conclusions: DSCMR is a feasible and safe test in the non-invasive cardiac evaluation of patients at risk of CAD prior to renal transplantation. A negative DSCMR study is associated with a very low rate of cardiac events. This would suggest that invasive coronary angiography can be safely omitted in these patients. Funding: This study was supported by a grant from The Gawthorn Trust.